Passive Control of Hydrodynamic Forces on a Circular Obstacle in a Transient Flow: FEM Computations - Ain, Qurrat Ul; Khan, Y.; Mahmood, Rashid; Alameer, A.; Majeed, Afraz Hussain; Faraz, N. (Frontiers in Physics, 2022)
Hydrodynamic forces are crucial in engineering applications; therefore, various research initiatives have been conducted to limit them. In this research, a passive control technique to investigate the fluid forces acting on a circular cylinder in a laminar flow regime is studied. The reliability of the usage of a splitter plate (passive control device) downstream of the obstacle in suppressing the fluid forces on a circular obstacle of diameter D=0.1 is presented. The first parameter of the current study is the attachment of splitter plates of various lengths (Li)with the obstacle, whereas the gap separation (Gi) between the splitter plate and the obstacle is used as a second parameter. The control element of the first and second parameters are varied from 0.1 to 0.3. For the attached splitter plates of lengths 0.2 and 0.3, the oscillatory behavior of transient flow at Re=100 is successfully controlled. For the gap separations 0.1 and 0.2, the suppression of vortex shedding is also observed. However, it is observed that a splitter plate of too short length and a plate located at an inappropriate gap from an obstacle are worthless. Moreover, the present study is extended for power-law fluid in the same domain, and maximum drag reduction is achieved using the same strategy as for Newtonian fluid. The finite element method is utilized as a computational strategy for complicated nonlinear governing equations. For a clear physical depiction of the problem, velocity and pressure plots have been provided. It is concluded that the presence of a splitter plate has suppressed the vortex shedding and the flow regime turns out to be steady, as is evident from the nonoscillatory drag and lift coefficients.